Isytiqâq Dalam Bingkai Ilmu Fiqhul Lughah dan Pendapat Para Ulama - Ahmad Sirfi Fatoni (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
This article examines isytiqâq within the framework of Fiqhul lughah and the opinion of scholars. Isytiqâq is important to be studied more deeply because it is one of characteristic of Arabic language and within it we can produce new vocabulary words that have never been found before. The impact is that Arabic language is getting richer and more dynamic. The research method used is descriptive-critical analysis. The data collection technique uses the observation method with the note. The findings obtained are: (1) there are three kinds of isytiqâq: a) Al-isytiqâq al-shaghir, b) Al-isytiqâq al-Kabir, c) Al-isytiqâq al-Akbar, (2) Arab scholars differed on the issue of the origin of isytiqâq and its scope. Some scholars argue that some words are musytaq and some aren’t musytaq. Meanwhile, other scholars argue that all words are musytaq. While some others suspect that all words are authentic, there are no words that are musytaq from other words; (3) The scholars who think that some words are musytaq and some aren’t musytaq are the opinions of scholars of Bashrah and Kufah. The scholars of Bashrah argue that mashdar is the origin of isytiqâq. Meanwhile, scholars of Kufah argue that fi’il is the origin of isytiqâq; (4) The relationship between language and isytiqâq has a reciprocal relationship.